CD47-mediated regulation of glucose and lipid metabolism: implications for the pathogenesis of MASLD - Jiang, Xinru; Zhao, Wei; Shen, Botao; Han, Yumeng; Chen, Kexin (Frontiers in Endocrinology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD), previously known as non-alcoholic fatty liver disease (NAFLD), has gradually become a leading cause of end-stage liver disease as a heterogeneous group of diseases. While the underlying mechanisms of MASLD remain incompletely understood, it is clear that glycolipid metabolism, coupled with subsequent disruptions in hepatic sinusoidal homeostasis and cellular senescence play significant roles in its onset and progression. In recent years, CD47 has been recognized not only as a critical target in cancer therapy but also as a participant in the development of metabolic diseases through complex signaling pathways. Increasing evidence suggests that CD47 is closely associated with the development of MASLD; however, its role in MASLD has not yet been widely explored. Therefore, this review aims to summarize current research on the potential role of CD47 in the pathogenesis of MASLD, particularly in relation to disturbances in glucose and lipid metabolism.